Environmental law for sustainable construction : a guide for construction, engineering and architecture professionals - Baker, Francine; Charlson, Jennifer (Emerald Publishing Limited, 2023)
Environmental Law for Sustainable Construction gives a practical overview of key areas of environmental law as it affects the construction sector. Clearly structured for ease of reference, the book provides coverage of core areas in a format that will help professionals and organisations to manage compliance issues relating to environmental law. It will also support the improvement of environmental protection and sustainable development. Coverage in the book includes * key areas of environmental regulation, including environmental impact and habitat assessments, climate change law, contaminated and brownfield land, waste management and water pollution * an overview of the UK planning process, and environmental regulators and their powers * environmental requirements on construction sites, and environment-related insurance matters * proactive project checklists to facilitate compliance. Environmental Law for Sustainable Construction is suitable for a broad range of practitioners in the architecture, engineering and construction (AEC) industry who require a clear introduction and reference to help navigate the complexity in this area of law. Dr Francine Baker LLB and MA (1st cl. Hons), PhD, FHEA, FCICES, MCIArb is a Solicitor of the Supreme Court of England and Wales (practising). Dr Jennifer Charlson MA (Oxon), MBA, PhD, CEng, FIET is a Solicitor of the Supreme Court of England and Wales (non-practising).
Includes index.
Keywords: Sustainable construction -- Law and legislation -- Great Britain.; Environmental law -- Great Britain.; Technology & Engineering, Construction -- General.; Building construction & materials.; elektronické knihy; electronic books